DIFFERENTIAL TREATMENT OF SUSPECTS IN COURT FROM THE PERSPECTIVE OF HUMAN RIGHTS AND LEGAL LOGIC - Suryasaputera, Ruswiati; Irianto, Bambang Sugeng (EQUALEGUM International Law Journal, 2025)
Background. Different legal practices can affect fairness and consistency in the justice system, the implications of different treatment of suspects in court from two different but interrelated perspectives: human rights and legal logic. The aim of this research was to analyze the impact of different treatment of suspects in court from the perspective of human rights and legal logic, by exploring how . Research Methods. The research method used includes comparative analysis and case studies, where this research will explore concrete examples of justice systems in various countries or jurisdictions that face similar dilemmas. Findings. The findings highlight that inconsistent treatment of suspects can undermine the fairness of legal proceedings, affect judicial outcomes, and pose challenges to human rights protection. This research explore how differences in treatment of suspects in court can influence the fairness of the legal process and its results, by considering aspects of human rights and consistency of legal logic, so that implementation can be implemented in the form of reform of the justice system, training and education, and strengthening law enforcement. Conclusion. The study emphasizes the necessity of justice system reforms, legal education, and strengthened law enforcement to address these disparities. Furthermore, effective implementation requires collaboration among governments, legal institutions, NGOs, and communities to ensure meaningful changes that enhance justice and uphold human rights.